Total Life Models - An Important Tool in Design of Quality - Morup, Mikkel (My University, 1993)
Product quality is far more than "fitness for use" and robustness in the manufacturing process. This paper discusses the phenomena of product quality in the entire product life. It presents a total life model which serves several purposes, such as expanding the design teams' understanding of quality and adding structure to total life scenarios in the specification phase.